2013
DOI: 10.1186/2110-5820-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of skin perfusion in mottling area during septic shock

Abstract: BackgroundMottling score has been reported to be a strong predictive factor during septic shock. However, the pathophysiology of mottling remains unclear.MethodsIn patients admitted in ICU for septic shock, we measured on the same area the mean skin perfusion by laser Doppler, the mottling score, and variations of both indices between T1 (6 hours after vasopressors were started) and T2 (24 hours later).ResultsFourteen patients were included, SAPS II was 56 [37–71] and SOFA score at T1 was 10 [7–12]. The mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 17 publications
0
43
0
5
Order By: Relevance
“…Several authors have shown that adjusting norepinephrine doses gradually, to achieve a MAP of 75 and then 85 mmHg, was beneficial in some patients, but frankly deleterious in others [12,15]. Likewise, the administration of norepinephrine improved small-vessel perfusion in some but not all patients [15,16]. These studies demonstrated that although a minimal threshold MAP is required to perfuse tissues, it is not sufficient to normalize the microcirculatory perfusion.…”
Section: Vasopressorsmentioning
confidence: 88%
“…Several authors have shown that adjusting norepinephrine doses gradually, to achieve a MAP of 75 and then 85 mmHg, was beneficial in some patients, but frankly deleterious in others [12,15]. Likewise, the administration of norepinephrine improved small-vessel perfusion in some but not all patients [15,16]. These studies demonstrated that although a minimal threshold MAP is required to perfuse tissues, it is not sufficient to normalize the microcirculatory perfusion.…”
Section: Vasopressorsmentioning
confidence: 88%
“…This technique has already been reported to assess skin perfusion alterations in non-cirrhotic patients with septic shock [12]. Laser light penetrates the tissue and is scattered and partly absorbed.…”
Section: Laser Doppler Assessment Of Skin Perfusionmentioning
confidence: 99%
“…During the last years, microcirculation alterations were established as the main cause of organ failure and death [8,9] and their persistence, despite global hemodynamic resuscitation, is an earlier and stronger predictor of outcome than global hemodynamic variables [10]. Among the tools developed to assess microcirculation alteration at the bedside, we recently developed a clinical score, called the mottling score, evaluating skin perfusion [11,12]. This simple and reproducible score clinically quantifies the mottling area extension around the knee.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of mottling prognosis value perfectly illustrates this point. Mottling is defined as patchy skin discoloration that usually starts around the knees due to heterogenic small vessel vasoconstriction, reflecting abnormal skin microperfusion [1]. More than 45 years ago, mottling was frequently noticed in patients with septic shock [2].…”
Section: Do Not Misquote Clinical Signsmentioning
confidence: 99%